PENGARUH DOSIS PUPUK KANDANG SAPI DAN KONSENTRASI THIDIAZURON TERHADAP PERTUMBUHAN BIBIT TANAMAN PORANG (Amorphophallus oncophyllus) - Dermawan, Muhammad Zuhri; Syukri, Syukri; Marnita, Yenni (University of Prof. Dr. Hazairin, SH, 2023)
This research aims to determine the effect of the dose of cow manure and the concentration of the growth regulator Thidiazuron on the growth of porang plant seeds. The design used was a factorial randomized block design consisting of 2 factors. Factor I, dose of cow manure, and factor II concentration of PGR Thidiazuron. This research concludes: (1) The dose of cow manure has a significant effect on the day shoots emerge, plant height at 75 DAP, stem diameter at 45, 60, and 75 DAP, and number of leaves at 75 DAP, and has a very significant effect on height. plants at 45 and 60 DAP and wet stover weight at 75 DAP, had no significant effect on the vigor index on the 7th day after DAP. (2) Thidiazuron PGR concentration had a very significant effect on the day of shoot emergence, vigor index on the 7th day of DAP, and plant height at 45 and 60 DAP, had no significant effect on plant height at 75 DAP, stem diameter at 45, 60 and 75 DAP, number of leaves 75 DAP and wet stover weight 75 DAP. (3) The interaction between the treatment dose of cow manure and the PGR concentration of Thidiazuron had a significant effect on the number of leaves. The best results from this research were in the treatment with a dose of cow manure of 15 g/polybag and a Thididazuron PGR concentration of 3 mg/l of water.